A triumphant decline?: Tetanus among slaves and freeborn in Brazil - Ian Read (História, Ciências, Saúde: Manguinhos, 2012)
Tetanus and other widespread endemic diseases of Brazil's early national period speak to intimate details of common life and give clues to big, vexing questions, such as why Brazil's population expanded dramatically at the turn of the twentieth century. Tetanus was for a long time one of Brazil's deadliest afflictions, especially among infants, but historians know very little about it. Using archival sources from across the Empire and early Republic, this article argues tetanus disproportionately killed the enslaved population, but gradually diminished in virulence for nearly all groups across the country by the second half of the 1800s. This decline should be attributed only partially to medical knowledge. Rather, indirect demographic and technological changes were more important factors in Brazil.